An agency mapping of marginalized communities and aid providers during the COVID-19 pandemic in Malaysia [version 2; peer review: 1 approved, 2 approved with reservations] - Melati Nungsari; Nicole Fong; Chuah Hui Yin; Veena Pillai (Wellcome Open Research)
Background: Given the urgent need for help amongst vulnerable populations throughout the coronavirus disease 2019 (COVID-19) pandemic, civil society organizations (CSOs) and members have stepped up to provide support for impacted communities. The process of responding to these urgent needs reflects the agency and resilience of civil society members in accessing or providing resources. There is still a lack of understanding of how human agency is exercised in the context of power imbalances. Such an understanding is important not only for creating an effective and inclusive aid delivery mechanisms but also improving preparedness for future public health and economic crises. Methods: This study utilizes Albert Bandura’s social cognitive theory to comprehensively map the agency landscape of aid providers and marginalized populations during the first few months of the COVID-19 pandemic in Malaysia. Assuming that these populations’ main goals are access to aid while providers’ main goals are to provide aid, this study categorizes the different modes of agency involved and highlights environmental facilitators and constraints for each of these groups in achieving their goals. Data was collected through in-depth interviews with 34 participants. Using a hermeneutic content analysis based on a sample of 824 textual excerpts from the interviews, we explore the relationship between each component of the agency landscape to understand the relationships between them. Results: We find that marginalized populations are often unable to achieve their goals despite clear intentions to survive. Additionally, we find that proxy agency is problematic for marginalized populations and characterize why this is the case. Conclusions: Finally, we present policy recommendations which prioritise marginalized populations and their needs, while removing barriers to accessing aid.